Pengaruh Belanja Subsidi, Belanja Hibah dan Belanja Bantuan Sosial terhadap Kemiskinan di Indonesia - Dinar Islami Sari; Feny Marissa (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Poverty is a complex, multi-dimensional problem in developing countries including Indonesia. Subsidy expenditure, grant expenditure and social assistance expenditure are government expenditures intended to help reduce poverty. This study aims to examine the effect of subsidy expenditure, grant expenditure and social assistance expenditure on poverty in Indonesia. This study uses a quantitative descriptive analysis method with multiple linear regression analysis techniques. The data used in this study are secondary data sourced from several agencies such as the Directorate General of Fiscal Balance (DJPK) and the Central Statistics Agency (BPS) for the period 2003 - 2022. The results show that simultaneously subsidy expenditure (energy and non-energy), grant expenditure, and social assistance expenditure have an influence on poverty in Indonesia, while partially energy subsidy expenditure and grant expenditure have an influence on poverty in Indonesia. However, non-energy subsidy expenditure and social assistance expenditure have no influence on poverty in Indonesia. This can occur because budget realization for grant expenditure and energy subsidy expenditure is prioritized in public policy to reduce poverty, while non-energy subsidy expenditure and social assistance expenditure occur due to inaccurate targeting in their distribution